My hero academia. Vol. 4, The boy born with everything - Horikoshi, Kohei, 1986-; Cook, Caleb D. (Shonen Jump manga., 2016)
When the U.A. High sports festival comes around, the budding heros are excited to show off and find a superhero mentor. The students must survive multiple rounds of competition as shadowy forces watch the academy, planning an attack.